2017
DOI: 10.1371/journal.pone.0176503
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of hepatitis C treatment using generic direct-acting antivirals available in India

Abstract: Background & aimsAvailability of directly-acting antivirals (DAAs) has changed the treatment landscape of hepatitis C virus (HCV) infection. The high price of DAAs has restricted their use in several countries. However, in some countries such as India, generic DAAs are available at much cheaper price. This study examined whether generic DAAs could be cost-saving and how long it would take for the treatment to become cost-saving/effective.MethodsA previously-validated, mathematical model was adapted to the HCV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 32 publications
1
80
1
1
Order By: Relevance
“…A modelling study showed that treatment of HCV infection using generic direct-acting antiviral drugs is cost-saving. 402 Provision of HBV oral drugs through the National Viral Hepatitis Control Program is currently in the planning stage.…”
Section: The Lancet Gastroenterology and Hepatology Commissionmentioning
confidence: 99%
“…A modelling study showed that treatment of HCV infection using generic direct-acting antiviral drugs is cost-saving. 402 Provision of HBV oral drugs through the National Viral Hepatitis Control Program is currently in the planning stage.…”
Section: The Lancet Gastroenterology and Hepatology Commissionmentioning
confidence: 99%
“…Despite these high costs, DAA treatment in the majority of patients has been found to be generally cost effective, with some regimens characterized as cost saving in the non-transplant population. 33,34 While early treatment regimens, such as those identified in this data set, were very expensive, competition from newly released agents has dramatically reduced the cost of treatment in an effort to increase market share. Treatment costs have also been reduced after shorter durations of care and have been demonstrated to be equally effective.…”
Section: Discussionmentioning
confidence: 99%
“…Regimens based upon these drugs have been shown not only to be safe and efficacious, but even cost-effective within 2 years, and cost-saving within 10 years of their initiation overall and within 5 years in persons with cirrhosis. 58 Pan-genotypic drugs will contribute to further reduce costs for HCV cure.…”
Section: Elimination In Low-re Source S E T Ting Smentioning
confidence: 99%